2018
DOI: 10.1002/jcsm.12307
|View full text |Cite
|
Sign up to set email alerts
|

Three cachexia phenotypes and the impact of fat‐only loss on survival in FOLFIRINOX therapy for pancreatic cancer

Abstract: BackgroundBy the traditional definition of unintended weight loss, cachexia develops in ~80% of patients with pancreatic ductal adenocarcinoma (PDAC). Here, we measure the longitudinal body composition changes in patients with advanced PDAC undergoing 5‐fluorouracil, leucovorin, irinotecan, and oxaliplatin therapy.MethodsWe performed a retrospective review of 53 patients with advanced PDAC on 5‐fluorouracil, leucovorin, irinotecan, and oxaliplatin as first line therapy at Indiana University Hospital from July … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
127
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(141 citation statements)
references
References 41 publications
12
127
1
1
Order By: Relevance
“…Muscle represents more than 40% of body weight, and thus, its wasting accounts for a large part of body weight loss in cachexia. Other organs also waste, however, including cardiac muscle and adipose tissue, two organs that clearly play an important role in cachexia and pancreatic cancer outcomes . Here, we observed wasting of skeletal muscle, heart, fat, and multiple other organs, as well as activin induction in most of those organs.…”
Section: Discussionmentioning
confidence: 53%
“…Muscle represents more than 40% of body weight, and thus, its wasting accounts for a large part of body weight loss in cachexia. Other organs also waste, however, including cardiac muscle and adipose tissue, two organs that clearly play an important role in cachexia and pancreatic cancer outcomes . Here, we observed wasting of skeletal muscle, heart, fat, and multiple other organs, as well as activin induction in most of those organs.…”
Section: Discussionmentioning
confidence: 53%
“…Evaluating muscle at a single specific time point may not help in predicting survival and could not evaluate muscle loss . These findings suggested that a longitudinal study of changes in body composition may provide a more comprehensive understanding of the impacts of body composition on outcomes …”
Section: Discussionmentioning
confidence: 99%
“…The consensus definition of cachexia in patients with cancer is weight loss greater than 5% or weight loss greater than 2% in already symptomatic patients who have a body mass index (BMI) less than 20 kg/m 2 . To simulate the definition of cachexia, patients with a reduction or increase in SMI, SMD, SMG, or TATI of ≥5.0% were classified as having ‘loss’ or ‘gain’, respectively …”
Section: Methodsmentioning
confidence: 99%
“…Similarly, radiotoxicity has been observed at higher rates in those undergoing stereotactic radiotherapy for locally advanced and borderline resectable malignancies with a preoperative diagnosis of SARC . Muscle and fat wasting during FOLFORINOX therapy for patients with pancreatic cancer was also independently associated with a poor overall survival . Routine body composition measurements before and during treatment may have a role in predicting poor neoadjuvant therapy outcomes in the future.…”
Section: Discussionmentioning
confidence: 99%